2021
DOI: 10.1177/17531934211042720
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors and mortality rates for non-traumatic upper extremity amputations

Abstract: Non-traumatic upper extremity amputations are an increasing concern with the rising prevalence of diabetes mellitus. To ascertain the risk factors and mortality rates for these amputations, the demographic information, amputation history, comorbidities and clinical outcomes of 140 patients who underwent non-traumatic upper extremity amputations between 1 January 2004 and 31 October 2017 were studied. Correlations were assessed using Cochran-Armitage chi-squared tests, odds ratios and multivariate binomial logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, literature on UEAs is limited, with just one single-center retrospective study on nontraumatic UEAs. 18 Our study aimed to identify the incidence rate and risk factors of 30-day MM and mortality in a large cohort of nontraumatic UEA patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, literature on UEAs is limited, with just one single-center retrospective study on nontraumatic UEAs. 18 Our study aimed to identify the incidence rate and risk factors of 30-day MM and mortality in a large cohort of nontraumatic UEA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, Ting et al demonstrated a notable divergence in the survival curves for major and minor nontraumatic UEAs. 18 Nontraumatic shoulder amputations are relatively rare and primarily indicated for cases requiring malignant tumor resection when distal amputation is not feasible. These procedures entail complex surgery involving extensive dissection near critical structures including the brachial plexus and subclavian vessels, increasing the risk of damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations